THE TRAINING MODEL OF FUTURE BIOLOGY TEACHERS TO ECOLOGICAL AND EDUCATIONAL ACTIVITY - Марія Скиба (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The article deals with the approaches of scholars to modeling of educational process. The training model of future biology teachers to ecological and educational activity is developed. The main components of this model - the purpose, the task, the principles, educational conditions and preparation stages as well as components (substantial, motivational, axiological, emotional and active) and the preparedness level of students to ecological and educational activity are characterized. This developed model gives the possibility to formulate goals of students' training to ecological and educational activity, to reflect the contents of educational materials, to choose methods and means of education, forms of organization, to control, grade and reflect the efficiency of students' training to ecological and educational activity, to emphasize the attention of students on realization of self-educational goals.